Analysis of factors affecting pulmonary tuberculosis incidence - Susanti, Febri Arini; Kasim, Ahmad Muhammad; Rahayu, Mesra (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Pulmonary Tuberculosis is an infectious disease caused by bacteria that can affect the lungs and other organs, specifically Mycobacterium tuberculosis. Mycobacterium belongs to a group of acid-fast bacteria commonly known as AFB (Acid-Fast Bacilli). To this day, pulmonary tuberculosis remains one of the most dangerous infectious diseases worldwide. This study aims to analyze the factors influencing the incidence of pulmonary tuberculosis. Research Methodology: This research employs an observational study with a case-control study design. The sample consists of 69 individuals diagnosed with pulmonary tuberculosis. The sampling technique used is purposive sampling. Data collection was conducted using questionnaires, and data analysis was performed using the chi-square test. Result: The results of this study indicate that occupation (p=0.000), income (p=0.000), housing conditions (p=0.000), and smoking (p=0.018) significantly influence the incidence of pulmonary tuberculosis. All variables examined in this study showed an impact on individuals affected by pulmonary tuberculosis. Conclusion: This study concludes that occupation, income, housing conditions, and smoking are significant factors influencing the incidence of pulmonary tuberculosis. Improving these factors may help reduce the prevalence of pulmonary tuberculosis in the community. Therefore, individuals are expected to adopt healthier lifestyles by maintaining cleanliness and a healthy home environment, making it a habit to cover their mouths when sneezing or coughing, and avoiding spitting indiscriminately. Additionally, they are encouraged to actively seek information about pulmonary tuberculosis and participate in educational sessions on the disease.